Achievement of Mathematics Teachers on Production of Computer Based Software Package for Teaching And Learning of Mathematics - Etukudo, Udobia Elijah (Faculty of Tarbiya and Teacher Trainning, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
The research was carried out to determine the achievement of mathematics teachers in the production of computer-based software packages for teaching and learning mathematics. Fifty (50) mathematics teachers of which twenty (20) were from primary schools, fifteen (15) from secondary schools and fifteen (15) were lecturers from, tertiary institutions, were selected for this study. They were trained on computer-based software package production for twenty-one (21) days and rated. The result of the analysis using ANOVA and t-test at 0.05 level of significance, shows that there was no significant difference in achievement of the teacher in computer-based software package production. Primary school teachers had mean achievement score of 73%, secondary 72%, lecturers 75%. Male had 75.6%, female 71.5%, t-ratio showed no gender difference at 0.05 level of significance. It is recommended that computer-based software production by teacher should be encouraged.